Youth project Space-π using small spacecraft for research of near-Earth space and remote sensing of the earth - Makarov, S. B.; Zavjalov, S. V.; Volvenko, S. V.; Aharonyan, A. K.; Avetisyan, V. H.
This work is devoted to the implementation of the scientific and educational project ”Space-π” for the development and production of small spacecraft on the domestic digital platform in order to implement schoolchildren’s projects. A very important part of this work is that a lot of school groups take part in it, not only from St. Petersburg, but from all over Russia in general, and in the future from other countries. They have the opportunity to participate via the Internet both in the processing of information and in the process of how the satellite is manufactured.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture